The Influence of Perceived Value, Service Quality on Customer Loyalty Mediated by Corporate Image - Janati, Anisah; Kusmayadi, Andri (PT Inovasi Pratama Internasional, 2024)
Perceived value an important role in marketing strategies that can be implemented by the banking industry by providing the best facilities for its customers to be able to provide trust, experience of the services provided so that the company's image increases and customers become loyal to the industry. The purpose of this study was to determine the greatest influence of customer loyalty. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire to 100 male and female BCA bank customer respondents aged 17-50 years and domiciled in Central Jakarta. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that 7 hypotheses submitted were accepted, and the perceived value variable has the greatest direct influence on the company's image. Then the greatest indirect influence is the company's image with perceived value and customer loyalty. This study contributes to the company in maintaining and improving the company's image can be seen from several consumer complaint factors optimally and measurably. For further research, the researcher suggests expanding the research area and looking for objects in other fields.